Effect of a phone reminder system on patient-centered tuberculosis treatment adherence among adults in Northwest Ethiopia: a randomised controlled trial. Issue 1 (25th June 2021) - Gashu, Kassahun Dessie; Gelaye, Kassahun Alemu; Lester, Richard; Tilahun, Binyam
Abstract : Objectives: This study aimed to evaluate the effect of the phone reminder system on patient-centred TB treatment adherence during continuation phase, where patients are responsible for taking medication at home. Methods: We conducted a two-arm randomised controlled trial on adult patients with TB during the continuation phase. In the intervention arm, patients received routine care plus phone-based weekly pill refilling and daily medication reminders. In the control arm, participants received only routine care. A covariate adaptive randomisation technique was used to balance covariates during allocation. The primary outcome was adherence to patient-centred TB treatment, and secondary outcomes included provider–patient relationship and treatment outcomes. We applied per-protocol and intention-to-treat analysis techniques. Results: We randomised 306 patients to intervention (n=152) and control (n=154) groups. Adherence to patient-centred TB treatment was 79% (110/139) in intervention and 66.4% (95/143) in control groups, with relative risk (RR) (95% lower CI) (RR=1.632 (1.162 to ∞); p=0.018, one tailed). Good provider–patient relationship was 73.3% (102/139) in intervention group and 52.4% (75/143) in control group, p=0.0001. TB treatment success was 89.5% (136/152) in intervention group and 85.1% (131/154) in control group, p=0.1238. Conclusions: Mobile phone-based weekly refilling with daily medication reminder system improved adherence to patient-centred TB treatment and provider–patient relationship; however, there was no significant effect on treatment success. Trial registration number: Pan African Clinical Trials Registry (PACTR201901552202539).